The Rock Melon: the story of a male's narcissism and his infidelity / Nurhafizah Ali ... [et al.] - Ali, Nurhafizah; Othman, Shamshad Begham; Mustapha, Aida; Muslim, Mazni (2018)
This paper is a psychological reading of K.S. Maniam's short story The Rock Melon exploring the concept of male's narcissicm and infidelity. This study investigates how the male character, who is an adulterer, views himself, his wife, and his sexual partner who happens to be none other than his sister-in-law. To understand the character's motives, the researchers utilize a theoretical framework of infidelity and narcissistic personality disorder (NPD) to study the male character's narration as well as his actions throughout the story. The findings suggest that the male character's infidelity is strongly influenced by his narcissistic personality disorder. His narcissistic personality disorder does not only cause troubles for himself, but also inflicts a more serious psychological damage on his relationship with others around him, especially his wife and his sexual partner.